Studi Literatur: Implementasi Pembelajaran Bermakna dalam Pembelajaran IPS di Sekolah Dasar - Mahayanti, Kadek; Lasmawan, Wayan; Kertih, Wayan (Pascasarjana UM, 2024)
The formation of character and social insight is very important for students to have since elementary school, which makes social studies learning very important to be taught. However, there is a big challenge in social studies learning in elementary schools, namely an interesting learning method in accordance with the development of elementary school students who are still at the concrete operational stage. One solution to overcome this challenge is to apply a meaningful learning approach. This approach makes it easy for students to understand new concepts because the concept is still related to the concepts that students previously had, so that learning becomes more effective. This study presents a guide for teachers in implementing social studies learning in elementary schools using a contextual and relevant meaningful learning approach. The main focus of this article is on how to design social studies learning through methods that can provide meaningful learning experiences for students. Thus, teachers are expected to be able to design and implement social studies learning that provides learning experiences that are appropriate to needs, and can provide understanding and social skills for students.